LINEAR ANNULAR ANTENNAS ARRAY DESIGN BY EVOLUTIONARY ALGORITHMS: A COMPARATIVE STUDY - Chaker, Hichem; Mehadji, Abri; Badaoui, Hadjira (Journal of Fundamental and Applied Sciences, 2022)
This paper exposes a comparative study that was made between the adaptive particle swarm optimization (APSO) and the hybrid model genetical swarm optimizer approaches (GSO) for the synthesis of 1-D equally spaced annular ring antenna arrays for both TM11 and TM12 modes. The synthesis of 1-D uniform antenna arrays is designed as a mono-objective problem. The employed optimization techniques are compared in terms of convergence rate and side lobes level reduction. Several original numerical results are provided to demonstrate the performance of the proposed techniques. The results reveal that the suggested array antenna synthesis approach using genetical swarm optimizer outperforms the adaptive particle swarm optimization in terms of side lobes level reduction and convergence rate.